Simulasi Luas Genangan Banjir Batang Sinamar Nagari Taram Kab. Lima Puluh Kota - Taufik, Arrahmat; Daud, Darwizal; Andriani, Andriani (Universitas Batanghari Jambi, 2025)
Batang Sinamar is located in Lima Puluh Kota Regency, West Sumatra Province, and flows through Riau Province before emptying into the Strait of Malacca. Flooding can cause loss of life and property. In the Nagari Taram area, floods occur almost every year with an average inundation depth of 1–2 meters. However, no research has been conducted on flood control and early warning systems. Meanwhile, the economic losses experienced by the community are significant. Therefore, it is necessary to conduct simulations of flood inundation depth and flood-prone areas as an initial study for flood control planning. The simulation uses HEC-RAS 6.4.1 software, QGIS, and the DEMNAS base map from BIG. Hydrological analysis is performed using the Nakayasu and Snyder Synthetic Unit Hydrographs with flood return periods of 2, 5, 10, and 25 years. The simulation results show that the flood inundation area increases with higher return periods. For the flood event in 2019, the discharge was equivalent to a 5-year return period flood, which was 982.18 m³/s, with an inundation area of 293.51 hectares. Hazard zones (marked in red) are predominantly found along the riverbanks, with an average distance of around 100 meters from the river's edge. The study concludes that the areas along the riverbanks are unsuitable for residential settlements, schools, and agricultural activities due to inundation depths of ≥3.0 meters.